Effects of waterborne polyurethane on storage stability, rheological properties, and VOCs emission of crumb rubber modified asphalt. (15th March 2022) - Zhao, Yuechao; Chen, Meizhu; Wu, Shaopeng; Jiang, Qi; Xu, Haiqin; Zhao, Zenggang; Lv, Yang
Abstract: Crumb rubber modified asphalt (CRMA) has been put forward and become a research hotspot due to the environmental pressure and the actual demand for road engineering. However, worrying issues such as poorer storage stability and more serious VOCs emissions have emerged one after another. In this work, waterborne polyurethane (WPU) was employed as the shell material to package the crumb rubber (CR) to prepare a porous composite modifier (CM) by solvent volatilization. The effects of WPU on storage stability, rheological properties, and VOCs release of CRMA were investigated. The experimental results indicate that the asphalt with CM as a modifier (CMMA) has better high temperatures storage stability than traditional CRMA. The temperature sweep experiment designates that CM can improve the high temperatures performance of the asphalt binder by increasing the rutting factor (G*/sin δ ) and complex modulus (G*), but the fatigue performance is slightly weakened. The direct tensile tests (DTT) demonstrate that the fracture energy of CMMA is slightly lower than that of CRMA but still 2.3 times that of virgin asphalt. Moreover, GC-MS test results prove that the VOCs emission of CMMA is extremely lower than that of CRMA and virgin asphalt. The nitrogen adsorption test of CM and CM's SEM images suggest that the inhibition mechanism of VOCs by CM might be the synergistic effect of adsorption and shielding. The conclusions of this study can provide a new method of cleaner production with a lower carbon footprint for building materials such as asphalt.